Exploring the Use and Perceptions of AI-powered Chatbots for Learning: A Survey of CIFS Students at WIUT (Eurasian Journal of Learning and Academic Teaching, 2024)
The use of AI driven chatbots in education is becoming more popular and is seen as a promising tool for enhancing students’ learning experiences. To gain a better understanding of how this technology impacts students, the study aimed to explore how students use AI chatbots for educational purposes and assess their overall perceptions and experiences when interacting with these virtual assistants. The survey was conducted among Level 3 students (n=160) at Westminster International University in Tashkent (WIUT). The goal of the survey was to determine how familiar students are with AI chatbots, how often they use them, what benefits they see, what challenges they face, and what changes they would like to see in the future. Data was collected using both qualitative and quantitative techniques through an online questionnaire comprising 15 questions. The results indicate that AI-powered chatbots are widely used in educational settings, offering benefits such as convenient information access, personalized assistance, resource accessibility and enhanced engagement levels. However, students highlighted challenges such as lack of human interaction, concerns regarding information accuracy, data privacy issues and limited customization options. Obtained results provide valuable insights for teachers and educational institutions looking to improve student learning experiences and engagement by implementing AI-powered chatbots. The findings could be further enriched by including a more diverse sample from different educational settings and using additional methods such as interviews and observations